Challenges and adversities among doctors in the era of healthcare disruption: Reflection from COVID-19 pandemic - Sugiyatmi, Tri A.; Hadi, Usman; Chalidyanto, Djazuly; Pathak, Yashwant; Miftahussurur, Muhammad (Narra Sains Indonesia, 2023)
The doctor's profession is noble and tied up with quite strict rules, both in terms of ethics as well as discipline. Naturally, there is a problem of asymmetrical information between doctors and patients, often leading to misunderstandings. The purpose of this review is to map the available evidence related to the challenges and difficulties faced by doctors in the era of disruption. The evidence indicate that disruption of health services has both positive and negative effects. Many aspects related to the use of technology in the medical practices including innovation, cost-effectiveness, and quality improvement. However, psychologically, the doctors often get frustrated by internal or external triggers. The external factors, ranges from the equipment and work procedures, for instance, using high technology, communication with management, inter-professional relationships, patients, and their families. Volatility, uncertainty, complexity, and ambiguity (VUCA) could cause stress and burnout. In this case, doctors are highly vulnerable, and consequently, have the potential to make mistakes. Therefore, the adversity faced by doctors ought to be mapped. Resilience is a barrier against stress and burnout and the ability to adapt in resilience among doctors is important factor in dealing with the disruption era.